An evolving view on biogeochemical cycling of iron - Kappler, Andreas; Bryce, Casey; Mansor, Muammar; Lueder, Ulf; Byrne, James M; Swanner, Elizabeth D (Nature reviews. Microbiology, 2021)
Biogeochemical cycling of iron is crucial to many environmental processes, such as ocean productivity, carbon storage, greenhouse gas emissions and the fate of nutrients, toxic metals and metalloids. Knowledge of the underlying processes involved in iron cycling has accelerated in recent years along with appreciation of the complex network of biotic and abiotic reactions dictating the speciation, mobility and reactivity of iron in the environment. Recent studies have provided insights into novel processes in the biogeochemical iron cycle such as microbial ammonium oxidation and methane oxidation coupled to Fe(III) reduction. They have also revealed that processes in the biogeochemical iron cycle spatially overlap and may compete with each other, and that oxidation and reduction of iron occur cyclically or simultaneously in many environments. This Review discusses these advances with particular focus on their environmental consequences, including the formation of greenhouse gases and the fate of nutrients and contaminants.